Jane Eyre: Now and Forever; or, the Strange Afterlife of Gothic - Allen, Emily; Felluga, Dino (Romanticism on the Net, 2004)
AbstractThis paper examines the recent fascination the Broadway musical has had with Victorian gothic, focusing both on the transition from opera seria to Disneyesque musical and on one specific cultural product, Paul Gordon and John Caird’s 2000 Broadway production, Jane Eyre: The Musical.  The paper claims that this particular hybrid of two notoriously hybrid nineteenth-century forms (the novel and opera) defangs both of its source genres, but nevertheless still allows its middle-class audience to participate in the spectacle of their own self-definition as consumers of “culture.”  The production also allows that audience to congratulate itself for having escaped the bourgeois repressions that arguably made the gothic such a viable genre in the Romantic and Victorian periods.  The fact is, though, that contemporary viewers of the Broadway gothic musical do still experience the frisson of a repressed terror: the return to a postmodern world that scripts our camp appreciation of such kitsch entertainments.